Characterizing and optimizing (co-)pyrolysis as a function of different feedstocks, atmospheres, blend ratios, and heating rates. (April 2019) - Liu, Jingyong; Huang, Limao; Xie, Wuming; Kuo, Jiahong; Buyukada, Musa; Evrendilek, Fatih
Highlights: (Co-)pyrolysis of sewage sludge and water hyacinth was compared in five atmospheres. Three kinetic analyses were used to estimate activation energy. Thermodynamic parameters (Log A, Δ H, Δ S, and Δ G ) were estimated. Activation energy of the blend was lower in CO2 than N2 atmosphere. Joint optimization of three responses was based on empirical models. Abstract: (Co-)pyrolysis behaviors were quantified using TG and Py-GC/MS analyses as a function of the two fuels of sewage sludge (SS) and water hyacinth (WH), five atmospheres, six blend ratios, and three heating rates. Co-pyrolysis performance, gaseous characterizations and optimization analyses were conducted. Relative to N2 atmosphere, co-pyrolysis was inhibited at low temperatures in CO2 atmosphere, while the CO2 atmosphere at high temperatures promoted the vaporization of coke. The main (co-)pyrolysis products of SS and WH were benzene and its derivatives, as well as alkenes and heterocyclic compounds. Average apparent activation energy decreased gradually with the increased atmospheric CO2 concentration and was highest (377.5 kJ/mol) in N2 atmosphere and lowest (184.7 kJ/mol) in CO2 atmosphere. Significant interaction effects on the mean responses of mass loss, derivative TG, and differential scanning calorimetry were found for fuel type by heating rate and atmosphere type by heating rate.